Long-term consequences of traumatic brain injuries with ice-hockey players - Sekretnyi, V.; Nekhanevych, O. (Journal of Education, Health and Sport, 2021)
Introduction: Significant part of sports related concussions (SRC) are below the level of clinical diagnosis of SRC or are unnoticed. The most severe cumulative consequence of SRC is chronic traumatic encephalopathy (CTE). The study of a wide range of clinical manifestations of CTE plays an important role.